POTENTIAL STAGNATION AND DECLINE IN RETURN ON INVESTMENT ~IDENTIFYING MEDIUM-TERM ISSUES IN AN INTENSIVE ENGLISH PROGRAM IN A JAPANESE UNIVERSITY~ - Lynch, Gavin (PEOPLE: International Journal of Social Sciences, 2019)
This research reports on five years of results of IELTS (International English Language Testing System) testing taken by first year university students in a Japanese university. The data analyzed in previous papers was from economics majors taking higher level English classes in the academic years of 2013 and 2014, and then in 2016 and 2017 by liberal arts (culture/tourism/English) majors in a new department whose initial focus was English. Lynch (2017) reported that “return on investment (ROI) in education increases when students are given choices in their education”, confirming earlier results found by Lynch & McKeurtan (2011), and Spokes (1989). Furthermore, teaching in a more intensive way (using a quarter system rather than a semester system) was found to give greater ROI. This study goes further and examines a further year of results, finding that stagnation and some decline in results began. This may indicate that the initial high results may have been partly due to special circumstances present in the new department, or that new circumstances have appeared which limited academic gains. Results are reported and discussed. Data and a discussion including class student-teacher ratio is added, giving a new direction to the research. Overall, despite decline in results, it was found that the continuing the intensive program is still worth it in terms of ROI for some years. Findings also included how changing university entrance examination requirements, teacher experience and burnout, and temporary dips in shown ability can all be important points of research.